Learning of Aqidah And Morals As A Character Education Method for Students Towards Parents, Teachers and Friends at MTS Nurul Hikmah Pasarkemis Tangerang - Yuningsih, Yuyu; Rohmat, Yusup (MANDAILING GLOBAL EDUKASIA, 2024)
This article examines the implementation of Akidah Akhlak learning as a method of character education for students at MTs Nurul Hikmah Pasarkemis. The focus of this study is to identify how Akidah Akhlak learning can shape students' character in interactions with parents, teachers, and friends. This study uses a qualitative approach with a case study method, which involves data collection through interviews, observations, and documentation. The results of the study indicate that Akidah Akhlak learning has a positive impact on the formation of students' moral attitudes, such as mutual respect, discipline, and a sense of responsibility towards parents, teachers, and friends. In addition, the implementation of Akidah Akhlak also plays an important role in creating a harmonious school environment and supporting students' personal development. This learning motivates students to care more about the values ​​of goodness taught in religion and strengthens positive social interactions between students and their surroundings. Therefore, this study recommends that Akidah Akhlak learning be strengthened and prioritized in the education curriculum in schools, as an integral part of efforts to build students' character and morality continuously.